Evaluasi Tingkat Keberdayaan Petani melalui Kapasitas Usaha Tani Kakao sebagai Dasar Penentuan Prioritas Intervensi Program Pemberdayaan di Desa Metun Sajau - Suprafmi, Muhadi; Sari, Stefina Liana (Jurnal Multidisiplin Indonesia, 2026)
This study aims to evaluate the level of farmer empowerment through cocoa farming capacity in Metun Sajau Village, Bulungan Regency, as a basis for determining priority interventions in empowerment programs. The research employed a quantitative evaluative approach based on index analysis. The study population consisted of 50 cocoa farmers, all of whom were included as respondents using a census method. Data were collected through a structured questionnaire comprising 25 indicators across five dimensions of farming capacity, namely information accessibility, decision-making, financial management, partnership capacity, and adaptability. Data analysis was conducted using an empowerment index (0–100) and gap analysis to identify priority areas for capacity strengthening. The results indicate that the level of farmer empowerment, as reflected in cocoa farming capacity, falls within the moderate category, with a total index score of 59.62. The dimensions of decision-making (70.80) and financial management (67.10) are categorized as relatively strong. In contrast, information accessibility records the lowest index value among the five dimensions (35.20), although it remains within the moderate category and exhibits the largest gap (64.80). These findings suggest that farmers’ operational capacity has been established; however, it is not yet fully supported by a solid foundation in information access and systematic risk management. Based on the evaluation results, program improvement recommendations are formulated progressively through the enhancement of information access, farm management practices, as well as networking and collective marketing. This study provides a data-driven evaluative basis for refining empowerment programs at the village level.